Composición de Ácidos Grasos en aceites de mayor consumo en el Perú - Hernández Fernández, Eloísa (1999)
It has been estimated the contents offat acids in 45 kinds of comercial oils that are consume in Peru (36 vegetal oils and 9 compound oils) by means of gas-liquid cromotography tecnique and using trifloruro de boro like steryficant agent; with finality to generate data thare are not availables until today.The oils which origen are not specified shawed oleico acid 17,3 - 43 g%; linoleico acid 33,4 - 57 g%; linolenico acid 0,1 -10 g%. In the benne, colza, wheat, lupin, corn, olive, pecan and, soy oil havefound a similar aspect in the contents 01 fatty acids. The compound oils contained: oleico acid 20 - 25 g%, linoleico acid 31 - 49%, linoleico acid 0.5 - 4,4%.Signifitively the essential fat acids are contained in the vegetal oils studied. The results indicate the importance of this kinds of oils in the human nutrition.